(untitled) (Praxis Educativa, 2023)
Governments and institutions such as UNESCO believe that Information and Communication Technologies (ICT) are required to achieve high-quality education. Many initiatives to create digital resources have arisen from Covid lockdowns and isolation periods to support the teaching and learning process. Some websites, most of them of low quality, allow students and teachers to share tools. Therefore, minimum quality standards must be established and assessment tools created, so teachers can make their own resources and evaluate those of third parties. The eDocente Innovation Laboratory of Arts and Humanities (LIDAH) research project aims to establish procedures to create and evaluate digital learning resources. The methodology is based on the evaluation of the educational tools through user experience (UX), checking whether the tools meet teachers’ and students’ needs and expectations as main users. Action guides and rubrics will then be established based on different evaluation techniques to generate and filter educationally efficient resources.